Penentuan Titik Pabrik PT. XYZ Menggunakan Metode Center of Gravity terhadap Volume produksi dan Biaya Pengiriman Barang ke Customer - Fitra, Adi; Suhendra, Suhendra; Putra, Fibi Eko (JURNAL TEKNIK INDUSTRI, 2023)
Location selection is importan in determining the operational company cost because it can determine the costs and profits of the company. In terms of operational location determination can improve the quality of a company's operations by guaranteeing the accuracy of delivery. The purpose of this study is to determine the best potential point of the targeted companies in the GIIC Cikarang area. The location (-6,38874697, 107,1811769) obtained is in the middle of the customer. With the right location, PT. XYZ can reduce transportation costs so that it can increase the company's profits in terms of transportation.